ANALYSIS OF THE MAIN NOTIONS OF J.RAWLS‘ "A THEORY OF JUSTICE" - Goda Izabelė Izabelė Venslauskaitė (Problemos)
The article presents and overviews the main concepts of "A Theory of Justice" by J. Rawls such as justice, subject of justice, ideas of cooperation and well ordered society, veil of ignorance, rationality of the original situation, principles of justice, the rule of maximum minimorum. The author presents an analysis of the basic notions of "A Theory of Justice" by evaluating the two aspects of comprehensiveness and avoidance of error. The evaluation of comprehensiveness proceeds along the lines of discussion with some critics of J. Rawls such as Benjamin R. Barber who claims that J. Rawls does not manage to choose between the influence of I. Kant and Th. Hobbes. The author argues that the theory of justice pre-sen-ted by Rawls satisfies the criteria of coprehen-si-ve-ness by being essentially a Kantian and not a Hobbesian conception. The argument for this is proved by finding essential simmilarities between the Kantian principle of authonomy and the original situation of choice behind the veil of ignorance simulated by Rawls. She argues that the relation between the Kantian and the contractarian point of views signalled by the theory is the problem of different levels of it. "A Theory of Justice" is the one that expresses particullar principles via the contract rather than finds them as an outcome of it. The second principle of the avoidance of error emerges as an answer to the question wheather J. Rawls’ aim to create a theory of pure procedural justice has been achieved. The answer to this question is ambivalent in the sense that the concept "pure procedural justice" has itself weaker and stronger interpretations. J. Rawls making distinction between procedural and substantial justice says that the difference between them is similar to the one between procedural justice and the justice of results. J. Rawls avoided error in the sense that he deduced the principles of justice defending the human rights of individuals from his Kantian premisses. But the author has doubts wheather Rawls managed to avoid an error in the case if pure procedural justice is unterstood in the stronger (strict Kantian) sense as something a priori deduced from the principles of reason by deliberation.